Late toxicity and long-term quality of life in survivors of cancer of the major salivary glands more than 5 years after diagnosis: a multi-national study - Singer, Susanne; Amdal, Cecilie Delphin; Bjordal, Kristin; Herlofson, Bente Brokstad; Astrup, Guro Lindviksmoen; Boehm, Andreas; Wöhner, Ulrike; Hammerlid, Eva; Gama, Ricardo Ribeiro; Jacinto, Alexandre Arthur; Jansen, Femke; Verdonck-de Leeuw, Irma M.; et al. (Head & neck, 2026)
Background Because salivary gland cancers (SGC) are rare and include different tumor subtypes, data on their long-term quality of life and late toxicities are sparse. Methods Multi-national study including SGC survivors more than 5 years after diagnosis. They completed the European Organisation for Research and Treatment of Cancer (EORTC) quality of life core questionnaire together with its head and neck cancer module and reported problems that were most bothering for them. Toxicity was clinically assessed. Results Altogether, 60 survivors from nine countries participated and reported dry mouth (mean score 37.2), use of painkillers (35.0), problems with sexuality (30.1), insomnia (28.9), fatigue (27.8), trismus (24.9), and sticky saliva (23.3). The most frequently mentioned long-term problem was dry mouth, mentioned by a third of all participants. The most frequent toxicities were hearing impairment, soft tissue fibrosis, dry mouth, and cranial neuropathies. Conclusions Dry mouth is a frequent and disturbing problem in SGC survivors.
Online veröffentlicht: 1. August 2025
Gesehen am 17.12.2025